2014
DOI: 10.1021/ic502181g
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Bulky Formamidinatosamarium(II or III) Complexes with C═O and C═S Bonds

Abstract: The preparation of a new heterobimetallic samarium(II) formamidinate complex and selected reactions of samarium(II) complexes and one samarium(III) formamidinate complex with benzophenone or CS2 are discussed. Treatment of the tris(formamidinato)samarium(III) complex [Sm(DippForm)3] 1 (DippForm = N,N'-bis(2,6-diisopropylphenyl)formamidinate, (CH(NC6H3-(i)Pr2-2,6)2) with potassium graphite in toluene yielded the dark brown heterobimetallic formamidinatosamarium(II)/potassium complex [KSm(DippForm)3]n 2. Divalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 65 publications
1
57
1
Order By: Relevance
“…TheS m2ÀO4(isocarbonyl) bond is significantly shorter than Sm2ÀO3(thf). TheW1 ÀC49(isocarbonyl) (1.891-(8) )i ss lightly shorter than the W1ÀC(terminal carbonyl) bonds (2.004(10)-2.024 (9) ,r eflecting their greater Lewis Acidity than Sm II .E vidence of the presence of Sm II is provided by absorptions at 608 and 671 nm in the solid state visible spectrum of 1.These are assigned to f!dand metal to ligand charge transfer transitions of divalent samarium. [19] Further support for the presence of the divalent samarium comes from the reaction of 1 with benzophenone generating atransient purple/red color,consistent with the formation of aradical.…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…TheS m2ÀO4(isocarbonyl) bond is significantly shorter than Sm2ÀO3(thf). TheW1 ÀC49(isocarbonyl) (1.891-(8) )i ss lightly shorter than the W1ÀC(terminal carbonyl) bonds (2.004(10)-2.024 (9) ,r eflecting their greater Lewis Acidity than Sm II .E vidence of the presence of Sm II is provided by absorptions at 608 and 671 nm in the solid state visible spectrum of 1.These are assigned to f!dand metal to ligand charge transfer transitions of divalent samarium. [19] Further support for the presence of the divalent samarium comes from the reaction of 1 with benzophenone generating atransient purple/red color,consistent with the formation of aradical.…”
Section: àmentioning
confidence: 99%
“…[7] Likewise, the less powerful reducing analogue YbCp* 2 has had some similar behavior, for example,t rapping of triiron-, [8a] hexairon-, [6] monocobalt-, [8b] and tricobalt [8c] carbonyl clusters.In seeking N-donor alternatives to the cyclopentadienyls for analogous purposes,w eh ave used the bulky [Sm-(DippForm) 2 2À from reaction with CS 2 . [9] In the search for another lanthanoid N-donor reductive trapping agent, we have now shown that the divalent samarium meso-octaethylcalix [4] [8b]…”
Section: àmentioning
confidence: 99%
“…Not only does the anionic NCHN bite provide a variety of different nitrogen-based coordination modes (e.g., monodentate κ(N), bidentate κ(N,N ), or various bridging modes e.g., µ-1κ(N):2κ(N ), µ-1κ(N,N ):2κ(N,N ) to list a few) [6,7], the nitrogen-bound aromatic substituents can also provide additional coordination modes. The potential to form metal-arene interactions, such as η 6 coordination, has been largely observed in group one chemistry [8][9][10][11][12][13], though some examples are known in f -block chemistry [14]. In almost all examples of this aromatic coordination, the phenyl rings contained alkyl-substituents in either the 2,6 positions (e.g., iPr, Et, Me), or in the 2,4,6 positions (e.g., Me).…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts the group one complexes of the non-fluorinated N,N′-di(aryl)formamidinate ligands [21][22][23], which readily retain coordinating solvent. Since then, we have expanded the use of fluorinated formamidinate ligands to f-block chemistry [9,16,17,[24][25][26][27][28], in a variety of different contexts [5]. One of the fluorinated formamidinate ligands used was N,N′-bis (2,6-difluorophenyl)formamidinate (DFForm) in both trivalent [16,17], and divalent [16] rare-earth complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24] The metal as well as the steric and electronic contributions of the ligands influence the way conversion of CO 2 will proceed. Another nonnegligible factor is the solvent employed.…”
Section: Introductionmentioning
confidence: 99%